Sfrazeologizowane struktury syntaktyczne jako specyficzne zjawisko rosyjskiego systemu składniowego - Wieliczko, Ałła (Studia Rossica Posnaniensia, 2010)
In this report we would like to present the main principles of study and description of phraseological units in Russian syntax. Phraseological units are described from the point of view of formal, semantic, and communicative aspects.